2016
DOI: 10.1530/erp-16-0020
|View full text |Cite
|
Sign up to set email alerts
|

Right heart function deteriorates in breast cancer patients undergoing anthracycline-based chemotherapy

Abstract: BackgroundCardiotoxicity from anthracycline-based chemotherapy is an important cause of early and late morbidity and mortality in breast cancer patients. Left ventricular (LV) function is assessed for patients receiving anthracycline-based chemotherapy to identify cardiotoxicity. However, animal studies suggest that right ventricular (RV) function may be a more sensitive measure to detect LV dysfunction. The purpose of this pilot study was to determine if breast cancer patients undergoing anthracycline-based c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
26
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 28 publications
(40 reference statements)
5
26
0
1
Order By: Relevance
“…More recently, a published study including 49 breast cancer patients undergoing anthracycline‐based chemotherapy reported that mean RV fractional area change (FAC), the important parameter of RV radial systolic function, decreased significantly from 48.3% to 42.1% ( P = 0.01) during a period of 3 months . Similar results were reported by Calleja et al, who followed 40 female patients with breast cancer treated with trastuzumab with or without anthracycline .…”
Section: Chemotherapy‐induced Rv Remodelingsupporting
confidence: 86%
See 3 more Smart Citations
“…More recently, a published study including 49 breast cancer patients undergoing anthracycline‐based chemotherapy reported that mean RV fractional area change (FAC), the important parameter of RV radial systolic function, decreased significantly from 48.3% to 42.1% ( P = 0.01) during a period of 3 months . Similar results were reported by Calleja et al, who followed 40 female patients with breast cancer treated with trastuzumab with or without anthracycline .…”
Section: Chemotherapy‐induced Rv Remodelingsupporting
confidence: 86%
“…Boczar et al used echocardiographic methods to follow 49 patients with breast cancer treated with anthracycline‐based chemotherapy and revealed significant worsening of RV longitudinal strain 3 months after therapy initiation (from −16.2% to −13.81%, P = 0.04) …”
Section: Chemotherapy‐induced Rv Remodelingmentioning
confidence: 99%
See 2 more Smart Citations
“…They supposed that the right ventricle has a larger volume and so, less mass and it works against lower afterload [17]. Boczar et al [18] studied RV in breast cancer patients who received anthracyclin, and they hypothesized that a thinner RV may be more sensitive to the toxicity of chemotherapy compared to the thicker LV but there are no other supportive data.…”
Section: Discussionmentioning
confidence: 99%